2001
DOI: 10.1007/bf02358599
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic potatoes expressing anErwinia pectate lyase gene — results of a 4-year field experiment

Abstract: SummaryFour potato lines of cv. D6sir6e that express the pectate lyase (PL) isoenzyme 3 of Erwinia carotovora subsp, atroseptica were examined in a 4-year field experiment with respect to plant development, tuber yield and resistance of tuber tissue to Erwinia soft rot. The PL3 degrades plant cell wall pectin into unsaturated oligogalacturonates eliciting plant defence responses. In one line, enzyme expression was controlled by the CaMV 35S promoter (C) and in three lines it was driven by the potato patatin B3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Moreover, Allefs et al (1995) found that the cultivars display a great variability in secondary metabolites, particularly phenolic compounds. Consequently, their susceptibility and responses of treatments are modulated by their faculty to produce phytoalexins, and to induce key enzymes like polyphenol oxidase (PPO) and phenylalanine ammonialyase (PAL) (Weber et al 1996;Wegener 2001). In conclusion, Streptomyces isolates OE7, OE11, OE12 and OE 53 showed a potential for controlling soft rot on potato and could be useful in integrated control against Pectobacterium ssp.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Allefs et al (1995) found that the cultivars display a great variability in secondary metabolites, particularly phenolic compounds. Consequently, their susceptibility and responses of treatments are modulated by their faculty to produce phytoalexins, and to induce key enzymes like polyphenol oxidase (PPO) and phenylalanine ammonialyase (PAL) (Weber et al 1996;Wegener 2001). In conclusion, Streptomyces isolates OE7, OE11, OE12 and OE 53 showed a potential for controlling soft rot on potato and could be useful in integrated control against Pectobacterium ssp.…”
Section: Discussionmentioning
confidence: 97%
“…Environmental conditions, e.g. weather (Wegener 2001) and fertilisation (Kumar et al 1991) can affect soft-rot resistance of potato tuber tissue. How far environmental conditions influence the ranking of cultivars remains to be established, but the use of coloured cultivars in potato breeding should not be a risk for increasing the susceptibility to soft rot in new cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…GM potato plants able to interfere with bacterial quorum sensing via expression of a lactonase gene, showed a higher level of resistance to the bacterial plant pathogen P. carotovorum (Dong et al ., ). Transgenic potato plants with increased production of 5‐O‐glucosyltransferase (Lorenc‐Kukula et al ., ) and pectate lyase (Wegener, ) also showed increased resistance to P. carotovorum . To date, however, our knowledge of root exudation in situ is limited, and the composition of root exudates is mostly determined in hydroponic culture conditions.…”
Section: Shaping the Rhizosphere Microbiomementioning
confidence: 99%